The rate of brain abnormalities on in utero MRI studies in fetuses with normal ultrasound examinations of the brain and calculation of indicators of diagnostic performance. Issue 7 (July 2019) - Griffiths, P.D.; Bradburn, M.; Mandefield, L.; Mooney, C.; Jarvis, D.
Abstract : AIM: To estimate the rate of unexpected brain abnormalities detected by in utero magnetic resonance imaging (iuMRI) in fetuses without abnormalities at ultrasonography (USS). MATERIALS AND METHODS: A prospective cohort study of pregnant women whose fetus had no structural brain (or body) abnormalities recognised on antenatal ultrasonography. Women were recruited from 12 centres across the UK and underwent iuMRI at 18 gestational weeks or more in the [blinded for review]. The imaging studies were reviewed by an experienced neuroradiologist. The positive and negative predictive values of both USS and iuMRI have been calculated by combining the results of this study with the results from the main [blinded for review] study. RESULTS: One hundred and ninety-eight pregnant women were recruited and underwent iuMRI of 205 fetuses. Brain abnormalities were shown on iuMRI in two fetuses that were not recognised on USS (one case of a focal cortical abnormality and one case of mild ventriculomegaly). The negative predictive value for USS was 99.5% and 100% for iuMRI. CONCLUSIONS: To the authors' knowledge, this is the first study comparing USS and iuMRI in low-risk pregnancies. USS has a comparatively high rule-out for fetal brain abnormalities and should remain the screening tool of choice. Highlights: Our findings support the use of USS as the primary screening method for brain imaging. Both USS and iuMR are able to confirm normal brain development of the fetus. Additional iuMR imaging is needed when abnormalities are detected on USS.